Ação coletiva e ambiente: as associações de catadores de papelão na cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
In the contemporary world, there are major concerns how to "meet the needs of the current population without compromising the ability of future generations to meet" (LEFF, 2001). Thus, the aim of this study was to assess socioeconomic and environmental associations and centers of recyclable cardboard in the city of Manaus. According to Calderoni (2003), Brazil boasts a performance well below the already achieved by several countries. In this context, we emphasize the importance of associations of collectors of recyclable cardboard in the city of Manaus as a form of collective action model and standard functionality. In the associations, the collectors of cardboard, occupy the public space, creating a separate pole for survival in society and the constitution of new identities, such as environmental educators. Thus, the associations are complex and can be scored as labor, collective action and organization, people who come together to promote collective action. Thus, this study will contribute to knowledge about the complex system of production chain of cardboard in the city of Manaus and this could contribute to the formation of public policy organizations and social actors involved in this matter. The survey was conducted among the associations and clusters of scavengers who work in collecting and marketing scrap of cardboard being recycled in the city of Manaus - AM. The methodological approach of this research aimed to gather and articulate concepts and tools relevant to the development of a study of collective action and environmental associations and centers of recyclable cardboard from Manaus - AM, through the use of a theoretical and methodological basis based on the collection of quantitative and qualitative data through the application forms of socioeconomic and semi-structured interviews. These instruments have sought to contribute to the assessment of social, environmental and economic associations and core collectors. In this sense, recycling cardboard is a great system that revolves around a number of categories as an alternative income generation and environmental sustainability for certain actors in society.
Keywords: Ação Coletiva; Sustentabilidade; Catadores; Collective Action; Collectors; Sustainability; CIÊNCIAS AGRÁRIAS